Living Life : Assessing Bureaucratic Complexity in Citizen-Government Interactions - Perotti, Valeria (World Bank, Washington, DC, 2018)
Bureaucratic complexity in citizen-government interactions can be an obstacle to accessing basic services and exercising civil rights. This paper presents a new methodology to collect contributor-based data on the regulatory framework and compliance burden of six key citizen-government interactions: (i) civil registration and identification, (ii) voting, (iii) paying taxes, (iv) access to health care, (v) access to education, and (vi) access to utilities. The methodology was tested in Chile, Ghana, India, and Vietnam, and it provided an overview of the legal and regulatory frameworks. In addition, the study offers some interesting observations: (i) two of the four economies moved toward including digital components to civil registration and identification systems, making it easier to register births/deaths and obtain an identification document; (ii) three of the four economies require a specific voter ID to cast a ballot, which can discourage citizens from engaging in elections; (iii) patients accessing certain services at primary health care facilities may experience longer waits for treatment than those seeking access to the same services in hospitals; and (iv) a student's ability to access quality education can be limited by school placement based on residential address in two of the four economies. The lessons learned suggest that future studies should use survey data collection to investigate the practical experience of citizens beyond procedures and legal requirements. In addition, focusing on fewer areas and including a larger set of countries could generate greater variability and more robust conclusions.